2010
DOI: 10.1155/2010/490406
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Activation of Toll-Like Receptor and Receptor for Advanced Glycation End Products in Preterm Birth

Abstract: Objective. Individuals with inflammation have a myriad of pregnancy aberrations including increasing their preterm birth risk. Toll-like receptors (TLRs) and receptor for advanced glycation end products (RAGE) and their ligands were all found to play a key role in inflammation. In the present study, we reviewed TLR and RAGE expression, their ligands, and signaling in preterm birth. Research Design and Methods. A systematic search was performed in the electronic databases PubMed and ScienceDirect up to July 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 91 publications
(108 reference statements)
0
33
0
5
Order By: Relevance
“…We focused on IL-1 to control. (G) Quantitative PCR of RAW-Blue macrophages treated with IL-1b (1 mg/ml) or vehicle with or without 101.10 (10 26 M) or Kineret (1.5 mg/ml) for and upstream TLR4 and TLR2 (66) pathways proposed by an abundance of literature to be implicated in triggering human PTB (67)(68)(69)(70); also, efficacy of 101.10 was shown in a relevant human cell line. Concordantly, in the current study, several mediators of inflammation were induced in our rodent models (e.g., IL-6, IL-8, and cyclooxygenase-2); yet, specific inhibition of IL-1R by 101.10 reduced PTB induced by every stimulus (IL-1, LPS, LTA) tested, highlighting its critical role.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on IL-1 to control. (G) Quantitative PCR of RAW-Blue macrophages treated with IL-1b (1 mg/ml) or vehicle with or without 101.10 (10 26 M) or Kineret (1.5 mg/ml) for and upstream TLR4 and TLR2 (66) pathways proposed by an abundance of literature to be implicated in triggering human PTB (67)(68)(69)(70); also, efficacy of 101.10 was shown in a relevant human cell line. Concordantly, in the current study, several mediators of inflammation were induced in our rodent models (e.g., IL-6, IL-8, and cyclooxygenase-2); yet, specific inhibition of IL-1R by 101.10 reduced PTB induced by every stimulus (IL-1, LPS, LTA) tested, highlighting its critical role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies demonstrated associations between elevated levels of circulating proinflammatory cytokines, particularly interleukin (IL) 6, IL-1beta, and tumor necrosis factor alpha (TNFalpha) and preterm birth . These inflammatory cytokines might link the pathology of uterine contraction, uterine cervical ripening, and preterm premature rupture of membranes (Noguchi et al, 2010). Stimulation of TLRs with their ligands has been shown to induce proinflammatory cytokine release in uterine epithelial cells, fetal membranes and placenta (Schaefer et al, 2004;Noguchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines might link the pathology of uterine contraction, uterine cervical ripening, and preterm premature rupture of membranes (Noguchi et al, 2010). Stimulation of TLRs with their ligands has been shown to induce proinflammatory cytokine release in uterine epithelial cells, fetal membranes and placenta (Schaefer et al, 2004;Noguchi et al, 2010). Moreover, the presence of TLR4 detected by immunohistochemistry in the amnios of women at labor suggested the possibility that stimulation of TLRs with their ligands induce proinflammatory cytokine release, conducting to labor (Schaefer et al, 2004;Noguchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…В целом исследования взаимосвязи между полиморфизмом ге-нов цитокинов, в том числе и наиболее изученного ФНО-α/G308A, риском преждевременных родов дали неоднозначные, и порой противоречивые результаты. Это, возможно, объясняется несколькими факторами: полиморфизмы тесно связаны с другими близлежа-щими функциональными изменениями гена; суще-ствуют ген-взаимодействия, которые определяют кли-нические проявления; этническое разнообразие изу-чаемых групп; иные важные воздействия окружающей среды полностью не учитывались или были исключе-ны при исследовании популяций [32].…”
unclassified
“…В последние годы появляются работы о роли механизмов врожденного иммунитета в репродук-тивной функции человека [32,33]. В развитии ряда патологических процессов, в том числе воспаления, имеют значение распознающие рецепторы врожден-ной иммунной системы toll-подобные рецепторы (TLRs), они обеспечивают интегрирующую и регу-лирующую роль в активации и реализации врожден-ного иммунного ответа на микробные патогены [33,34].…”
unclassified